2014
DOI: 10.1007/s00192-014-2573-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for urinary incontinence in women 65 years and older: a systematic review

Abstract: The suburethral sling procedure improves continence as well as QoL among elderly women with SUI; however, evidence is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
6
1
1
Order By: Relevance
“…GPs in this study were also not inclined to refer older women with co-morbidity to a specialist because of perceived risks of complications after surgery. However, evidence is inconclusive about differences in complication rates between older and younger women who underwent surgery for their incontinence [38]. These discrepancies between practice and evidence correspond with the findings from literature of well-known facts that women with urinary incontinence receive suboptimal treatment [10, 14].…”
Section: Discussionmentioning
confidence: 60%
“…GPs in this study were also not inclined to refer older women with co-morbidity to a specialist because of perceived risks of complications after surgery. However, evidence is inconclusive about differences in complication rates between older and younger women who underwent surgery for their incontinence [38]. These discrepancies between practice and evidence correspond with the findings from literature of well-known facts that women with urinary incontinence receive suboptimal treatment [10, 14].…”
Section: Discussionmentioning
confidence: 60%
“…The published information on SUI surgery in older women (≥65 years of age) is sparse. A 2015 systematic review evaluated RCTs and prospective non‐randomized trials published from 1966 to October 2013 . Only five studies fulfilled the inclusion criteria and all were about suburethral slings.…”
Section: Variables Confounding Outcomes Of Surgery For Uimentioning
confidence: 99%
“…A 2015 systematic review evaluated RCTs and prospective non-randomized trials published from 1966 to October 2013. 80 Only five studies fulfilled the inclusion criteria and all were about suburethral slings. Persistent SUI after surgery varied between 5.2% and 17.6%, and one study evaluating QoL showed significant improvement after surgery.…”
Section: Outcomes Of Surgery For Uimentioning
confidence: 99%
“…We observed that a woman's age and BMI had relatively little impact on the gynaecologists' recommendations for surgical treatment. This corresponds to an increasing body of evidence indicating that surgical treatments are effective in obese and in elderly patients [18][19][20][21][22]. On the other hand, it is also generally accepted that clinical decision-making is more complex given that overall health and functional status is poorer in these patient groups [21].…”
Section: Characteristics Levelsmentioning
confidence: 98%